Haptic-assistive technologies for audition and vision sensory disabilities. (19th May 2018) - Sorgini, Francesca; Caliò, Renato; Carrozza, Maria Chiara; Oddo, Calogero Maria
Abstract: Purpose: The aim of this review is to analyze haptic sensory substitution technologies for deaf, blind and deaf–blind individuals. Method: The literature search has been performed in Scopus, PubMed and Google Scholar databases using selected keywords, analyzing studies from 1960s to present. Search on databases for scientific publications has been accompanied by web search for commercial devices. Results have been classified by sensory disability and functionality, and analyzed by assistive technology. Complementary analyses have also been carried out on websites of public international agencies, such as the World Health Organization (WHO), and of associations representing sensory disabled persons. Results: The reviewed literature provides evidences that sensory substitution aids are able to mitigate in part the deficits in language learning, communication and navigation for deaf, blind and deaf–blind individuals, and that the tactile sense can be a means of communication to provide some kind of information to sensory disabled individuals. Conclusions: A lack of acceptance emerged from the discussion of capabilities and limitations of haptic assistive technologies. Future researches shall go towards miniaturized, custom-designed and low-cost haptic interfaces and integration with personal devices such as smartphones for a major diffusion of sensory aids among disabled. Implications for rehabilitation: Systematic review of state of the art of haptic assistive technologies for vision and audition sensory disabilities. Sensory substitution systems for visual and hearing disabilities have a central role in the transmission of information for patients with sensory impairments, enabling users to interact with the not disabled community in daily activities. Visual and auditory inputs are converted in haptic feedback via different actuation technologies. The information is presented in the form of static or dynamic stimulation of the skin. Their effectiveness and ease of use make haptic sensory substitution systems suitable for patients with different levels of disabilities. They constitute a cheaper and less invasive alternative to implantable partial sensory restitution systems. Future researches are oriented towards the optimization of the stimulation parameters together with the development of miniaturized, custom-designed and low-cost aids operating in synergy in networks, aiming to increase patients' acceptability of these technologies.